Memahami tingkah laku remaja bermasalah dari perspektif teori tingkah laku, humanistik, psikoanalitik & tret personaliti - Khalim Zainal (Universiti Kebangsaan Malaysia, 2008)
Human performs an incredible variety of acts, all considered human behavior. When a certain behavior is performed not according to certain sets of rules, it is considered as misbehavior. Thus misbehavior means an individual actions that disrupt, destroy, defy, hurt or infringe on others rights. Discipline is tied directly to misbehavior. It is intended to suppress, control and redirect that sort of behavior which includes specific categories of acts as cruelty, disrespect, boisterousness, cheating, fighting, sarcasm, defiance and apathy. Such misbehavior reduces effectiveness and pleasure in human relationship. This paper will discuss misbehavior among teenagers from the perspectives of Behavioral, Humanistic, Psychoanalytic and Personality Theory Trait